Transformasi Sikap dan Pemahaman Guru terhadap Siswa Disabilitas Melalui Pelatihan Pendidikan Inklusi - Novembli, Meta Silfia; Hasanah, Nisaul (Jurnal Pendidikan dan Pengajaran, 2024)
Inclusive education is organized so that all children, including children with disabilities, get quality education opportunities and services. However, the implementation of inclusive education raises several problems, one of which is teachers who do not understand inclusive education and disabilities, so they have difficulty accepting students with disabilities and managing classes well. This study aims to analyze the effect of inclusive education training on improving teachers' knowledge and attitudes in teaching students with disabilities. The methodology in this study used an experimental method with a one-group pretest-posttest design, which obtained a sample of 19 teachers. The data collection method was a closed questionnaire with an adapted and modified teacher attitude instrument and a teacher knowledge instrument compiled by the researcher based on the Inclusive Education Implementation Guide and the Inclusive Education Implementation Pocket Book in Elementary Schools. The analysis method used Wilcoxon, showing differences in teachers' knowledge and attitudes towards students with disabilities before and after being given inclusive education training. This study implies that teachers can apply more inclusive learning steps and recognize the characteristics of children with special needs. Thus, it can be concluded that inclusive education training can improve teachers' knowledge and positive attitudes in teaching students with disabilities.